Approach of optofluidics from optics to photonics - Liu, Ai Qun. (2013)
Microfluidics represents the science and technology that processes or manipulates a small amount of fluid (10-9 to 10-18 litres) with dimensions of tens to hundreds of micrometers in a microfluidic chip. Optofluidics aims in manipulating light and fluid at microscale and exploiting their interaction to create highly versatile devices that have significant scientific interests in many areas. The novelties of the integrated optofluidics are two-fold. First, fluids can be used to carry substances for analysis in highly sensitive optical micro-devices. Second, fluids can also be exploited to control light, making them tunable, reconfigurable and adaptive. It is a new breakthrough research area that provides new solutions and opportunities for a wide range of traditional photonic devices, allowing tuning and reconfiguration at the micrometer scale by using microfluidic manipulation. This new innovation allows scientists and researchers to tackle many classical problems with new tools and new research ideas. In this paper, the state-of-the-art of optofluidic research is reviewed with breakthrough innovations in optical and photonic devices, including the high potential applications of optofluidics in biophysical, biochemistry and biomedical studies.